An Assessment of Basic Patient Safety Skills in Residents Entering the First Year of Clinical Training. Issue 2 (June 2018) - Comunale, Mark E.; Sandoval, Mathew; Broussard, La Toya
Abstract : Objectives: During safety rounds, we observed few residents demonstrating hand hygiene and patient identification as they began their postgraduate clinical training. We assessed baseline performance of these 2 basic safety skills in residents entering the first year of postgraduate clinical training (PGY1). Methods: PGY1 residents beginning training on July 1, 2013, and July 1, 2014, at our institution were examined using a simulated scenario testing for hand hygiene and patient identification. Nurse volunteers posed as patients and evaluated each resident using a standardized scoring tool. Residents were observed for the following behaviors when interacting: (1) hand hygiene before or upon entry into the patient's room (HHE); (2) resident introducing himself or herself (INTRO); (3) resident identifying patient (IDNB); (4) resident comparing patient's stated name and date of birth to patient's ID band (IDC); (5) resident explaining procedure to patient (EXP); and (6) resident performing hand hygiene upon exiting patient's room (HHL). Results: A total of 114 residents were examined. Compliance results were as follows: HHE at 66% (75); INTRO at 96% (110); IDNB at 52% (59); IDC at 42% (48); EXP at 90% (103); and HHL at 58% (66). Conclusions: Developing and hardwiring basic patient safety skills is essential for creating an institutional culture of safety. We used a simulated patient scenario to provide a baseline assessment of 2 important safety skills. The results obtained demonstrate poor compliance with hand hygiene and patient identification. Our results suggest that there is a need for additional training and perhaps new methods of training and reinforcement in medical school and beyond, to hardwire these basic patient safety skills.